Sistem Informasi Geografis Berbasis Web Digitasi Persil Bangunan - Arief Susanto (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2015)
Geographic Information Systems ( GIS abbreviated as Geographic Information System ) is a specialized information system that manages data having spatial information . Most to process data in the form of GIS data are still many who use desktop application or can only run on one computer while the more advanced development requires us to produce information more easily is to develop a GIS online ( via the Internet ) and can be accessed Anywhere You . This application is designed using DFD modeling and created using the programming language PHP with MySQL database as well as utilizing Google Map API . As well as to facilitate the collection of data by the field of local government development . Moreover , the existence of GIS aims to help local governments in the search for building plots parcels and ownership of data previously not been structured to be more structural and facilitate spatial data collection .